2009
DOI: 10.4049/jimmunol.0803041
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Sequestered in the Liver Suppress the Proinflammatory Response of Kupffer Cells to Systemic Bacterial Infection

Abstract: The liver plays a major role in clearing bacteria from the bloodstream. Rapid clearance is primarily the function of fixed tissue macrophages (Kupffer cells) that line the hepatic sinusoids. Although Kupffer cells play a critical role in blood clearance, the actual elimination of the bulk of bacteria taken up by the liver depends upon the accumulation of bactericidal neutrophils. Subsequent experiments demonstrating neutrophils inside Kupffer cells derived from infected animals prompted our speculation that ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 53 publications
(56 reference statements)
2
33
0
1
Order By: Relevance
“…Neutrophils have demonstrated regulatory properties in the setting of hemorrhagic shock by down-regulating IL-6 within the liver and lungs [36]. Neutrophils are recognized as being able to modulate macrophages in sterile inflammation and single pathogen infection models [37,38], but the effects of neutrophils on inflammatory monocytes have not been reported previously. Daley et al [37] showed elevated levels of TNF and superoxide anion release from wound macrophages when neutrophils and presumably inflammatory monocytes were depleted with ␣Gr1 in the polyvinyl alcohol sponge wound model of inflammation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Neutrophils have demonstrated regulatory properties in the setting of hemorrhagic shock by down-regulating IL-6 within the liver and lungs [36]. Neutrophils are recognized as being able to modulate macrophages in sterile inflammation and single pathogen infection models [37,38], but the effects of neutrophils on inflammatory monocytes have not been reported previously. Daley et al [37] showed elevated levels of TNF and superoxide anion release from wound macrophages when neutrophils and presumably inflammatory monocytes were depleted with ␣Gr1 in the polyvinyl alcohol sponge wound model of inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…It is well established that ingestion of apoptotic cells can suppress the proinflammatory phenotype of effector immune cells, including macrophages [40 -43]. In a model of systemic listeriosis, Holub et al [38] demonstrated that apoptotic neutrophils suppressed the proinflammatory response after being ingested by Kupffer cells. Neutrophils are short-lived cells with a halflife of 6 -10 h and upon activation, undergo spontaneous apoptosis [44].…”
Section: Discussionmentioning
confidence: 98%
“…Bacteria engulfed by KCs are then internalized and killed by neutrophils through adhesion molecules CD11b/CD18 and CD54. The rapid elimination of bacteria as a result of a close interaction between KCs and neutrophils is apparently beneficial to liver host defenses [88,89]. In endotoxin-associated or ischemia/reperfusion liver injury, production of TNF-␣ or cytokine-induced neutrophil chemoattractant (CINC) by KCs has been shown to contribute to neutrophil adhesion and infiltration into hepatic sinusoids [90,91].…”
Section: Kupffer Cells and Neutrophilsmentioning
confidence: 99%
“…YopM could indirectly influence production of chemokines that signal through CCR2 in spleen by downregulating expression of cytokines, such as IL-1␤ and TNF-␣ (25), that activate ECs (33,45) Liver structure, function, and response to infection are distinct from those in spleen (23,40). In liver sinusoids, Kupffer cells (KCs) and neutrophil-KC interactions are prominent in the response to bacterial infection (16,17,20). KCs themselves are not potent antibacterial cells, but they bind bacteria avidly and present them to PMNs for killing (15)(16)(17)29).…”
Section: Cd11bmentioning
confidence: 99%